The Provision of Lyrics: Developing Children’s Socio-Emotional Development - Fachriyyati, Dyah; Muzaroah, Hilda (Indonesian Journal of Early Childhood Education Studies, 2015)
This research presents children’s socio-emotional development in terms of  the provision of  lyrics. It was conducted at Tarbiyatul Athfal Kindergarten, Jepara with 23 correspondence in experiment group and 21 students in the control group. The aim of  this research knowing if  provisioning a song lyrics has an impact on the children's social emotional development. The type of  this research was a quantitative research. The researcher used three methods to collect the data; they were observation, questionnaire, and documentation. An analysis technique that researcher used was population record analysis, first stage data analysis and last stage data analysis.The results of  this research showed percentage increasing for experiment group in the amount of  26,97% and 18,11% for the control group. If  the emotional development went well, the social development will develop as emotional development. Because, both has important thing with social development correspond to the age of  children.